Influence of Brand Image on Customer Attitude, Intention to Purchase and Satisfaction: the Case of Start-Up Brand Pomie Bakery - David G. Abin; Deske W. Mandagi; Lefrand. S Pasuhuk (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to analyze the influences of brand image on customer attitude, intention to purchase, and customer satisfaction in the context of start-up businesses, in which its research information could be a helping hand, especially for a start-up business. In particular, this research attempts to answer three main research questions. First, does the brand image affects the customer attitude? Second, does the brand image affect the intention to purchase? Third and last, does the brand image affect customer satisfaction? To answer these questions, a survey was conducted on 234 Pomie Bakery customers through questionnaires adopted from previous studies. The data has been analyzed using Structural Equation Modeling (SEM) using the SmartPLS software. The data analysis has proven that other than the variable of brand image’s influence on purchase intention, each correlation between other variables is significant. The result of this research is generally useful for start-up businesses as a reference in implementing brand strategies. By paying attention to the brand image, start-up businesses will benefit from consumer behavior in terms of customer attitude, intention to purchase, and customer satisfaction.